An unusual mechanism of building up of a high magnetization blocking barrier in an octahedral alkoxide Dy3+-based single-molecule magnet. Issue 5 (4th January 2021) - Long, Jérôme; Tolpygin, Aleksei O.; Mamontova, Ekaterina; Lyssenko, Konstantin A.; Liu, Dan; Albaqami, Munirah D.; Chibotaru, Liviu F.; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract : We report a new octahedral luminescent SMM exhibiting massive crystal-field splitting and an anisotropic barrier of 1385 cm −1 . Abstract : We report a new octahedral [Dy(OCPh3 )2 (THF)4 ][BPh4 ] luminescent Single-Molecule Magnet (SMM) exhibiting massive crystal-field splitting and an anisotropic barrier of 1385 cm −1 . Magnetic measurements combined with ab initio analysis reveal a novel mechanism behind the high blocking barrier based on the quenching of one-phonon transitions between the three low-lying crystal-field multiplets due to large energy gaps between them exceeding the available phonon energies and forcing the activated relaxation to proceed through the fourth doublet. The observed nonetheless short relaxation time is due to appreciable non-axial anisotropy, which opens a tunnelling relaxation path via interaction with the nuclear spins. Reducing the equatorial crystal-field quenches drastically the quantum tunnelling of magnetization, allowing for full exploitation of the high blocking barrier of the complex as in the best known SMMs.